2021
DOI: 10.1175/jas-d-20-0110.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Monsoon Rainfall to Changes in the Latitude of the Equatorward Coastline of a Zonally Symmetric Continent

Abstract: Recent studies have shown that the rapid onset of the monsoon can be interpreted as a switch in the tropical circulation, which can occur even in the absence of land-sea contrast, from a dynamical regime controlled by eddy momentum fluxes to a monsoon regime more directly controlled by energetic constraints. Here we investigate how one aspect of continental geometry, that is the position of the equatorward coastal boundary, influences such transitions. Experiments are conducted with an aquaplanet model with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Interestingly, the critical latitude here is similar to the critical latitude to form a land monsoon (Dirmeyer, P. A. 1998; Hui & Bordoni, 2021). Hui and Bordoni (2021) found that only when the southern coastline of an NH continent extended into the deep tropics (i.e., 20°N), the NH monsoon transformed from an oceanic monsoon into a land monsoon.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Interestingly, the critical latitude here is similar to the critical latitude to form a land monsoon (Dirmeyer, P. A. 1998; Hui & Bordoni, 2021). Hui and Bordoni (2021) found that only when the southern coastline of an NH continent extended into the deep tropics (i.e., 20°N), the NH monsoon transformed from an oceanic monsoon into a land monsoon.…”
Section: Resultssupporting
confidence: 63%
“…1998; Hui & Bordoni, 2021). Hui and Bordoni (2021) found that only when the southern coastline of an NH continent extended into the deep tropics (i.e., 20°N), the NH monsoon transformed from an oceanic monsoon into a land monsoon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…essential for the onset, removing land in the tropical latitudes prevents the rapid transition into the angular-momentum-conserving monsoon regime (Hui & Bordoni, 2021).…”
mentioning
confidence: 99%